Landscape and vacation preferences of urban dwellers in Buenos Aires (Argentina) - Faggi, Ana (2010)
Landscape forms define different kinds of activities and influence tourists’ and visitors’ expectations. Knowledge of users’ typology is a fundamental aspect to be considered in sustainable tourism. In this study we analyze the public perception associated with preferences for landscape and tourist destination. Surveys were applied to users visiting five urban nature reserves in the metropolitan area of Buenos Aires. Experiential and experimental preferences for landscape features were classified in ten cate gories; vacation was discriminated in beach, mountain, city and rural destinations and both were contrasted with the profiles and education levels of respondents on the background of Argentina as a country with high landscape diversity. There were significant differences between education levels and landscape preferences for four features : variety, one element of the landscape, sensorial features and color; while age was significant for six landscape features: maintenance, one element of the landscape, variety, wilderness, admiration and sensorial features. Beach landscapes, followed by mountain landscapes, were the preferred destinations selected by all groups of respondents, except for the group of people with elementary school education who chose rural destinations as their second preference.